Enhancing Students' High-Order Thinking Skills through STEM-Blended Learning on Kepler's Law During Covid-19 Outbreak - Haryadi, Rudi; Situmorang, Robinson; Khaerudin, Khaerudin (Jurnal Penelitian dan Pembelajaran IPA, 2021)
This study aimed to examines the effectiveness of the implementation of STEM-Blended learning to enhance high school students' high-level thinking skills on Kepler law concept during covid-19 outbreak. The method used in this study is a quasi-experimental method. This study used two class groups including the experimental class and the control class. This study was conducted at one of high schools in Indonesia. The students' higher-order thinking skills for the experimental class was included in the medium category with a percentage of achievement of 75%. However, in the control class, it was included in the medium category with a rate of 61%. The results showed that there were significant differences between experimental and control classes with the value .0015 < 0.05, meaning that the implementation of STEM-Blended learning is effective to enhance high school students' high-level thinking skills on Kepler law concept. This findings will be usefull for the development of STEM Education during Covid-19 outbreak.